Organizational Goals and Expected Behavior of American Managers - England, George W. (Academy of Management Journal, 1967)
This study complements the Journal March issue article by the author on ?Personal Value Systems of American Managers.? In the current analysis the author compares four levels of organizational goals with their assumed behavior importance and content. Organizational Efficiency, High Productivity and Profit Maximization form a subset of goals that are behaviorally very important and are viewed as maximization criteria and as alternative generators.